2012
DOI: 10.1007/s10815-012-9885-9
|View full text |Cite
|
Sign up to set email alerts
|

CASA derived human sperm abnormalities: correlation with chromatin packing and DNA fragmentation

Abstract: Purpose The present study was undertaken to evaluate the effects of morphokinetic abnormalities of human spermatozoa on chromatin packing and DNA integrity and possible beneficial effects of sperm selection in ICSI. Methods Semen samples from 1002 patients were analysed for morphology and motility using CASA. Protamine status and DNA fragmentation were analysed by chromomycin A3 staining and sperm chromatin dispersion assay respectively. Results Sperms with elongated, thin, round, pyri, amorphous, micro and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
7

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
(69 reference statements)
3
21
0
7
Order By: Relevance
“…Similarly, Abdelrazik et al [50] analyzed sperm morphology using computer assisted morphometry, and demonstrated that spermatozoa with several abnormal forms (in particular amorphous and micro heads) containing immature chromatin and higher DNA fragmentation rate compared with other forms of head abnormalities resulting in an increase in aneuploidy incidence and mutations in the germ line [44,51]. In the present study, it was demonstrated that DNA fragmentation was significantly higher in teratozoospermic men compared with normozoospermic men, similar to the results shown by several authors [44,48,50,52,53].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Abdelrazik et al [50] analyzed sperm morphology using computer assisted morphometry, and demonstrated that spermatozoa with several abnormal forms (in particular amorphous and micro heads) containing immature chromatin and higher DNA fragmentation rate compared with other forms of head abnormalities resulting in an increase in aneuploidy incidence and mutations in the germ line [44,51]. In the present study, it was demonstrated that DNA fragmentation was significantly higher in teratozoospermic men compared with normozoospermic men, similar to the results shown by several authors [44,48,50,52,53].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have found that the sperm DNA fragmentation index (DFI) had a significant correlation with sperm concentration [517], morphology [51819], and motility [192021]. However, controversy remains regarding the correlations between the DFI and semen parameters because some authors did not observe significant correlations between the sperm DFI and morphology [22], concentration [1821], or motility [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while speculative, our findings suggest little added utility of including semen phenotypes for predicting which couples may experience delays in conceiving based upon semen characteristics. We note, on the other hand, that there is some evidence suggesting that morphologically abnormal spermatozoa may be associated with chromosomal abnormalities or alterations in chromatin packing and DNA fragmentation, which in turn may impact fertilization (Tang et al ., 2010; Sivanarayana et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%